2018
DOI: 10.18267/j.pep.639
|View full text |Cite
|
Sign up to set email alerts
|

Is a Model of Comprehensive Regionalism Trade-Increasing for V4 Countries? Sectoral Approach

Abstract: This paper aims to identify the impact of a "deep" (economic union) and "shallow" (Common Commercial Policy) integration on 4 Visegrad countries' trade with the EU and non-EU industrialized countries. Trade flows are analysed on the basis of sectors over the period of 1995-2011: the gravity model also utilizes sectoral value-added and sectoral output as proxies for the market size. The impact of regional trade agreements (RTAs) is evaluated for 17 WIOD sectors based on the research methodology developed by Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The most pronounced effect of imports is observed for EBIT when imports fall or if the increase in imports is smaller than the increase in exports and net exports rise. This corresponds with the findings in the V4 countries according to the study by Gauger and Sledziewska [14]. However, during the period under review, the furniture industry lost its comparative advantage due to a negative trade balance because of the growth in imports in Slovakia and the decline in exports in Czechia.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The most pronounced effect of imports is observed for EBIT when imports fall or if the increase in imports is smaller than the increase in exports and net exports rise. This corresponds with the findings in the V4 countries according to the study by Gauger and Sledziewska [14]. However, during the period under review, the furniture industry lost its comparative advantage due to a negative trade balance because of the growth in imports in Slovakia and the decline in exports in Czechia.…”
Section: Discussionsupporting
confidence: 86%
“…The studies by Reppas and Christopoulus [12] and Cetin [13] revealed indirection by assessing the causality between international trade and macroeconomic growth. The impact of European integration on Visegrad countries trade using more advanced econometric techniques, examined by Gauger and Sledziewska [14], showed the influence on trade of higher value-added goods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Visegrad Group also engaged in foreign policy and regional cooperation. The group has played a role in Ukraine's development and has functioned as a communication platform to intensify dialogue between Ukraine and the EU (Gauger & Sledziewska, 2018). The Visegrad countries have shown interest in cooperation with the Mashriq region, including Jordan, Israel and Egypt (Döring, 2019).…”
Section: Brief History and Relations Of The V4 Group Of Countriesmentioning
confidence: 99%